Computerised Information Security Using Texture Based Fuzzy Cryptosystem - Alghamdi, A. A. (Engineering, Technology & Applied Science Research, 2018)
The main objective of this study is to form a unique and economical steganographic technique for digital pictures employed for secret transmission using texture and fuzzy logic. This technique is employed to embed data in the carrier image and to extract the hidden message within the same carrier image. Initially, fuzzification is completed which transforms the carrier and the secret image into numerous bitplanes. Afterward, the pixel number calculation is completed within the original image. Then feature extraction is completed within the secret image so as to represent the data in it. Finally, pixel merging follows within the sender region by assignment of white and black pixels in the original image and in the secret pictures. Pixel numbers and texture features are extracted and can be used as a key for retrieving the embedded image from the receiver. This modified approach can be applied in various images. Experimental results reveal that this method will hide and retrieve the secret messages in a carrier accurately.